Magnitude and factors associated with anemia among pregnant women admitted to labor ward of Hiwot Fana Specialized University Hospital, Eastern Ethiopia. (September 2021) - Abdu, Serkalem; Ali, Tilahun; Debella, Adera; Assefa, Nega; Teji Roba, Kedir
Objectives: Anemia is a common medical problem among pregnant women that will influence pregnancy and birth outcomes. In Ethiopia, there is a paucity of evidences regarding the problem among pregnant women admitted to labor ward. Therefore, the objective of this study was to assess the magnitude and factors associated with anemia among pregnant women admitted to labor ward for deliveries at Hiwot Fana Specialized University Hospital, Eastern Ethiopia. Methods: A cross-sectional study was conducted among 314 pregnant women admitted to labor ward at Hiwot Fana Specialized University Hospital in June 2020. Data were collected using an interviewer administered questionnaire and were entered into EpiData and analyzed using SPSS. Descriptive statistics and multiple logistic regression analysis were done to identify predictors of anemia. Results: In this study, the magnitude of anemia was 37.9% (95% confidence interval: 32.4, 43.0). Short birth interval (adjusted odds ratio = 2.5; 95% confidence interval: 1.02, 6.13), history of blood loss during pregnancy (adjusted odds ratio = 4.3; 95% confidence interval: 1.86, 9.9), less consumption of citrus fruit within a week (adjusted odds ratio = 2.9; 95% confidence interval: 1.2, 6.9), and meal frequency less than three times per day during pregnancy (adjusted odds ratio = 2.2; 95% confidence interval: 1.0, 4.6) were significantly associated with anemia, respectively. Conclusion: This study pointed out that more than one-third of pregnant women affected by anemia. Thus, interventions that could reduce anemia, such as counseling about increasing of meal frequency during pregnancy, foods rich in iron, and prevention and management of blood loss are recommended.